Synthesis, electrochemistry, in-situ spectroelectrochemistry and molecular structures of 1,4-naphthoquinone derivatives - KOCA, ATIF (ELSEVIER, 2021)
A novel series of 1,4-naphthoquinones substituted containing sulfur, nitrogen, oxygen atoms were synthesized. The structures of the novel products were characterized by using the various spectroscopic techniques such as H-1 nuclear magnetic resonance (NMR), C-13 NMR, mass spectrometry (MS), Fourier transform infrared spectroscopy (FT-IR) and microanalysis. The crystal structures of 2,3-bis(benzylsulfanyl)-1,4-napthoquinone 4 and 2,3-bis(ethylsulfanyl)-1,4-naphthoquinone 7 were determined by using X-ray single crystal diffraction method. Electrochemical behaviors of some 1,4-naphthoquinone (NQ) derivatives 3, 4, 7, 8, 9, 10, 12, 13, 15, 16, 17, 19 and 20 were studied by using cyclic voltammetry, square wave voltammetry and in-situ UV-Vis spectroelectrochemistry. The substituents of the NQ derivatives significantly altered the redox mechanism. In-situ UV-Vis spectroelectrochemical analyses of NQs supported the proposed redox mechanism. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Naphthoquinones; Spectroelectrochemistry; Electrochemical behaviors; Cyclic voltammetry; in-situ UV-Vis spectroelectrochemistry; Crystal structure